Antidepresant effects of Cinnamon (Cinnamomum burmannii) extract in depressed induced rats using 3-minutes Tail Suspension method - Nita Parisa; Mayasari Mayasari; Nia Savitri Tamzil; Bintang Arroyantri; Ziske Maritska (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Abstract Background. The increasing prevalence of depression gives rise to challenges in not only elucidating its diverse causes, but also in finding an effective treatment. One of the factors linked to depression is the imbalance of serotonin, norepinephrine, and dopamine neurotransmitters. Cinnamon (Cinnamomum burmannii) as one of the world’s wellknown cooking ingredients is believed to be able to regulate the neurotransmitters imbalance with the help of terpenoids and flavonoid polyphenols as one of its content. Objective. This study aims to determine the effectiveness of cinnamon extract as an antidepressant in depressed induced animal model. Methods. An experimental in vivo with pre-post control group design was conducted in twenty five Wistar strain white rats that were divided into 5 treatment groups that received fluoxetine as positive control, aquades, and different dose of cinnamon extracts (50 mg/kgBW, 100 mg/kgBW, and 200 mg/kgBW). Depression induction method used was 3-minute Tail Suspension Test, done for 14 days. The antidepressant effectiveness test was carried out by calculating the immobility time duration with Forced Swimming Test method and was further analyzed using one-way ANOVA test. Results. One-way ANOVA test results showed that there were differences in the mean duration of immobility time between treatment groups after being given cinnamon extract (p value = 0,000). Groups that were given 100 mg/kgBW cinnamon extract and 200 mg /kgBW showed a p value>0.05 when compared with positive control group receiving Fluoxetine although displayed a similar reduced immobility time. Conclusion. Cinnamon (Cinnamomum burmannii) extract showed a promising potential as an effective antidepressant tested in animal model. Keywords: cinnamon, extract, depression, immobility time, rat